2016
DOI: 10.1186/s12885-016-2715-1
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis with anti-TIF-1γ antibodies as a presenting symptom of underlying triple-negative breast cancer: a case report

Abstract: BackgroundDermatomyositis is an autoimmune myopathy characterized by proximal muscle weakness, muscle inflammation, and typical skin findings. It is a rare disease with an incidence of ~1/100 000. About 15–30 % of adult-onset cases are caused by underlying malignancy and dermatomyositis can be the first symptom of undiagnosed cancer, mainly in the case of anti-transcription intermediary factor 1γ (anti-TIF-1γ) antibodies presence. TIF-1γ is a transcriptional cofactor which is implicated in TGFβ signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…In patients with severe disease, steroid pulse of intravenous mPSL 1000 mg for three consecutive days is also an option for treatment. In addition, the introduction of IVIG or immunosuppressive medications such as methotrexate, azathioprine, cyclophosphamide, or ciclosporin is another option if the patient does not respond to steroid therapy or suffers adverse side effects [ 9 , 29 ]. Although these internal treatments are essential for the control of DM, the risk of surgical treatment will increase due to the immunocompromised effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with severe disease, steroid pulse of intravenous mPSL 1000 mg for three consecutive days is also an option for treatment. In addition, the introduction of IVIG or immunosuppressive medications such as methotrexate, azathioprine, cyclophosphamide, or ciclosporin is another option if the patient does not respond to steroid therapy or suffers adverse side effects [ 9 , 29 ]. Although these internal treatments are essential for the control of DM, the risk of surgical treatment will increase due to the immunocompromised effect.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, patients with early-stage disease could firstly undergo surgery according to the cancer stage in Table 1 . Conversely, the patients with initial internal treatment include unresectable cancers, in which surgical resection itself is not applicable at the point of diagnosis [ 9 , 13 , 20 , 22 , 24 , 26 ]. Table 2 (c) shows the relationship between the maximum creatine kinase level and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the presence of specific myositis-related autoantibodies (MSA) is associated with different clinical manifestations. The finding of high levels of anti-TF1γ and anti-NXP2 is frequent in paraneoplastic forms (about 80%) and often these patients have severe skin manifestations and dysphagia; a recent meta-analysis showed that patients with high levels of anti-TF1γ have a 27-fold higher odds ratio of developing malignancy [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no guidelines or randomized trials for the management of breast cancer complicated by dermatomyositis. The literature is based exclusively on case reports [1,2,4,6,8,[11][12][13][14][15][16][17][18][19]. The existing reports do not clearly indicate whether an immediate or postponed surgical approach to neoadjuvant therapy is preferable.…”
Section: Discussionmentioning
confidence: 99%
“…While a rare disease, with an incidence of approximately 1/100,000, adult-onset dermatomyositis is associated with a concomitant malignancy in 15-30% [34]. Paraneoplastic polymyositis may herald a yet undiagnosed malignancy or coincide with a tumor diagnosis.…”
Section: Paraneoplastic Myositis and Polymyositismentioning
confidence: 99%